2005
DOI: 10.3171/jns.2005.102.2.0382
|View full text |Cite
|
Sign up to set email alerts
|

Femoral nerve palsy secondary to traumatic pseudoaneurysm and iliacus hematoma

Abstract: The authors report a case of traumatic femoral nerve palsy caused by a pseudoaneurysm of the iliolumbar artery and a iliacus muscle hematoma. This case report details not only the classic history and physical findings seen in patients such as this one, but also illustrates an unusual source of the hematoma and a discussion of its treatment. A 20-year-old man was assaulted and presented to the authors's institution with a 1-week history of severe pain in the left anterior thigh and groin, weakness in the left q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
33
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(33 citation statements)
references
References 13 publications
(25 reference statements)
0
33
0
Order By: Relevance
“…Avulsion of the periosteum covering the internal surface of the iliac bone is prone to damage the nutrient vessels, mostly branches arising from the iliolumbar artery [12]. In a few cases in the literature, the authors observed a small pseudoaneurysm in the vicinity of these nutrient foramina [4,13,14]. For some authors, the presence of these aneurysms may explain brisk bleeding from the medial and inferior walls of the subperiosteal cavity during surgery [2,8].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Avulsion of the periosteum covering the internal surface of the iliac bone is prone to damage the nutrient vessels, mostly branches arising from the iliolumbar artery [12]. In a few cases in the literature, the authors observed a small pseudoaneurysm in the vicinity of these nutrient foramina [4,13,14]. For some authors, the presence of these aneurysms may explain brisk bleeding from the medial and inferior walls of the subperiosteal cavity during surgery [2,8].…”
Section: Discussionmentioning
confidence: 99%
“…This semiological aspect requires further discussion as this distinction was not always made in similar cases in the literature. Based on the published images, numerous cases reported as "intramuscular" iliac hematomas [13,14,[17][18][19][20][21][22] may actually have been subperiosteal hematomas (Table 3). Interestingly, all these patients were under 22 years old, further supporting the theory of periosteal avulsion.…”
Section: Clinical Manifestationsmentioning
confidence: 98%
See 1 more Smart Citation
“…The treatment of the disease may differ depending on the severity of symptoms and underlying disease. If the hematoma is small or there is evidence of clinical improvement, conservative treatments such as bed rest, correction of blood coagulation disorder and transfusion are preferred (7). Treatment decision about this clinical entity depends on the speed of onset, the size of hematoma and the degree of neurological impairment.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 Iatrogenic injury may occur as a result of the lithotomy position, prolonged traction, thermal injury or laceration. 4 The reported incidence of iatrogenic injury ranges from 0.2% to 0.4%.…”
Section: Introductionmentioning
confidence: 99%